Sir Thomas More's utopia: Glimpses of a Presence in 16th century portuguese chroniclers - Avelar, Ana Paula (2021)
In the 16th century the encounter with new spaces in Africa, Asia, or America, meant for European countries a questioning of their own conventional identities. Portugal assumed then a nuclear role in the way Europe has to know the Other - different places and different peoples. Sir Thomas More’s Utopia fictionally mirrors the Portuguese role in the unveiling of new worlds, namely through Raphael Hythlodaeus’ character, the traveller who tells about his presence in an ideal land. Eventually this paper analyses the dialogue between Portuguese 16th century chroniclers and More’s text.